(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Echocardiography has been used to noninvasively image the moving structures of the heart. This has proven particularly beneficial in pediatrics as echocardiography is a safe and portable imaging modality that can detect structural and functional abnormalities of the heart in real time. As ultrasound technology has improved, echocardiography has become the primary mode of diagnosing most pediatric heart disease, both congenital and acquired. The performance of a high-quality echocardiogram requires familiarity with the ultrasound principles involved in obtaining diagnostic images as well as a clear understanding of cardiac anatomy and imaging planes.